2014
DOI: 10.1080/09540121.2014.913764
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related behavioral risk factors among older female sex workers in Guangxi, China

Abstract: Objective Previous literature suggests a high rate of HIV infections among older female sex workers (FSW) in China. However, limited data are available regarding HIV-related behavioral risk factors among this population. In the current study, we aim to examine the demographic and behavioral factors that place older FSW at a high risk of HIV infection. Methods We conducted secondary analysis of the 2010 National Sentinel Surveillance (NSS) data from Guangxi China. A self-administered, standard behavioral surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…First, estimated HIV risk was higher for FSWs aged 22 and older. This finding is consistent with previous research that associated older female sex workers’ age with higher rates of infectious diseases including HIV [17, 18]. This finding can be explained by the fact that older women could simply have a longer exposure to risky behaviors since a considerable number of Ukrainian FSWs do not use condoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, estimated HIV risk was higher for FSWs aged 22 and older. This finding is consistent with previous research that associated older female sex workers’ age with higher rates of infectious diseases including HIV [17, 18]. This finding can be explained by the fact that older women could simply have a longer exposure to risky behaviors since a considerable number of Ukrainian FSWs do not use condoms.…”
Section: Discussionsupporting
confidence: 92%
“…Older age was another factor associated with higher prevalence of HIV, syphilis infections, unprotected sex, and injection drug use [17, 18]. Furthermore, low-tier FSWs with lower formal education levels were the more vulnerable for acquiring and transmitting HIV, HCV, and syphilis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Women who grew up in resource-poor settings usually lacked opportunities of education and skills training. Without job-related skills, these women may lack the opportunities to find alternative jobs and engage in sex work for their livelihood and to support their families [2,13,15,16]. With little or no formal education and few alternative employment opportunities, they tend to continue sex work for a longer duration [16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that there is a variation of HIV risk behaviours among FSWs in different age groups [10,11]. The available evidence suggests that older age (≥ 35 years) is a potent predictor of HIV, syphilis, and risk behaviours among FSWs [2,12,13]. Older FSWs are considered as disadvantaged groups compared to their younger FSWs in the competitive sex world.…”
Section: Introductionmentioning
confidence: 99%
“…Younger FSWs enter the sex trade at a younger age and typically do not have the financial burden of supporting a family. [7][8][9] In fact, after younger FSWs make enough money they usually quit the sex industry in their 30s to open small private businesses.…”
mentioning
confidence: 99%